2022
DOI: 10.1002/sstr.202200343
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancy Introduction to Increase the Capacity and Voltage Retention in Li‐Excess Cathode Materials

Abstract: Li‐rich rocksalt oxides are promising cathode materials for lithium‐ion batteries due to their large capacity and energy density, and their ability to use earth‐abundant elements. The excess Li in the rocksalt, needed to achieve good Li transport, reduces the theoretical transition metal redox capacity and introduces a labile oxygen state, both of which lead to increased oxygen oxidation and concomitant capacity loss with cycling. Herein, it is demonstrated that substituting the labile oxygen in Li‐rich cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
(132 reference statements)
0
6
0
Order By: Relevance
“…This is the deepest microscopic reason for the changed thermodynamic characteristics of solid oxide materials. The most direct effect of intrinsic OVs on the electronic structure is the breakage of charge balance in the system, which leads to reduced oxidation states for TMs such as Mn, Ni, and Co. 32,43,95 Cui et al 25 observed that intrinsic OVs produced during sintering resulted in a lower Mn ion valence (Mn 3.93+ vs. Mn 3.98+ ) in the bulk of OV-enriched Li-rich oxide Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2Àx synthesized through constant hightemperature sintering compared to non-isothermal sintering. After soaking the Li-rich material Li 1.2 Mn 0.6 Ni 0.2 O 2 with hydrazine hydrate solutions, Liu and co-workers detected a small amount of Mn 3+ produced on the surface of the treated oxygendeficient sample Li 1.2 Mn 0.6 Ni 0.2 O 2Àd based on Mn L-edge soft X-ray absorption spectra (sXAS) in the total electron yield (TEY) mode.…”
Section: Thermodynamics Of Intrinsic Ovsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is the deepest microscopic reason for the changed thermodynamic characteristics of solid oxide materials. The most direct effect of intrinsic OVs on the electronic structure is the breakage of charge balance in the system, which leads to reduced oxidation states for TMs such as Mn, Ni, and Co. 32,43,95 Cui et al 25 observed that intrinsic OVs produced during sintering resulted in a lower Mn ion valence (Mn 3.93+ vs. Mn 3.98+ ) in the bulk of OV-enriched Li-rich oxide Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2Àx synthesized through constant hightemperature sintering compared to non-isothermal sintering. After soaking the Li-rich material Li 1.2 Mn 0.6 Ni 0.2 O 2 with hydrazine hydrate solutions, Liu and co-workers detected a small amount of Mn 3+ produced on the surface of the treated oxygendeficient sample Li 1.2 Mn 0.6 Ni 0.2 O 2Àd based on Mn L-edge soft X-ray absorption spectra (sXAS) in the total electron yield (TEY) mode.…”
Section: Thermodynamics Of Intrinsic Ovsmentioning
confidence: 99%
“…Band structure: reproduced with permission. 95 Copyright 2022, John Wiley & Sons, Inc. Phase structure: reproduced with permission.…”
Section: Thermodynamics Of Intrinsic Ovsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, doping material is an efficient strategy for the enhancement of the absorbed light in the visible region which is favourable for effective solar cells, photo-electrochemical water splitting, and hydrogen storage [32,33]. However, other research works suggested the creation of oxygen vacancies to improve photocatalytic properties [34][35][36], furthermore, manipulation and control of the Oxygen's interstitial sites could help researchers produce more active O-rich oxide photocatalysts for water oxidation [37]. On the other hand, DFT simulation is designed to predict many aspects of energy harvesting and light up-conversion such as dye-sensitised solar-cells [38][39][40], thermoelectricity [41][42][43], and photocatalysis [36,44], also, it is regarded as a valuable tool with good reproducibility [45].…”
Section: Introductionmentioning
confidence: 99%